Study on Ajuga reptans Extract: A Natural Antioxidant in Microencapsulated Powder Form as an Active Ingredient for Nutraceutical or Pharmaceutical Purposes - Tiziana Esposito; Francesca Sansone; Giulia Auriemma; Silvia Franceschelli; Michela Pecoraro; Patrizia Picerno; Rita P. Aquino; Teresa Mencherini (MDPI AG, 2020)
The administration of natural antioxidants is considered to be a prevention strategy for chronic diseases and a useful tool for the healthcare system to reduce the administration of expensive and often not effective treatments. The chemical characterization of a methanolic extract (AJ) of Ajuga reptans L. was performed, and its antioxidant activity was evaluated. AJ and the major compounds, characterized by chromatographic techniques as phenylpropanoids and iridoids, were able to reduce the Reactive Oxygen Species levels in cancer cell lines (melanoma, A375, cervical cancer, HeLa, and alveolar adenocarcinoma, A549), stimulated by E. coli lipopolysaccharide. However, a clinical translation of these results encountered a significant limitation represented by the poor water solubility and bioavailability of the extract and compounds. Consequently, a hydro-soluble powder system (AJEP3) was developed by spray-drying encapsulating AJ into a multi-component solid matrix that is based on L-proline and hydroxyethylcellulose as loading and coating agents, and lecithin as solubility enhancer. The technological approach led to a satisfactory process yield (71.5%), encapsulation efficiency (99.9%), and stability. The in vitro water dissolution rate of the bioactive compounds appeared to be improved with respect to the extract, suggesting higher feasibility in the manufacturing and administration; even the in vitro biological activity of the produced multi-component AJEP3 was clearly enhanced.